Toxicity mediated oxidative stress and its mitigation strategies in crop plants - Batra, Shivani (Journal of Environmental Engineering and Landscape Management, 2021)
Oxidative stress occurs in plant due to various environmental stressors like drought, high temperature, pathogen invasion, heavy metals, pesticides etc. when plant faces these conditions, reactive oxygen species (ROS) are produced in the chloroplast, mitochondria, plasma membrane, peroxisomes, ER and cell wall due to the leakage of electrons. Depending upon its concentration the role of ROS is decided if less then it will act as a signaling molecule but if in excess it will damage the cellular machinery of plants as the production of species like free radicals would take place. Though to combat these stress plants have antioxidant defense machinery which include enzymatic and non- enzymatic which lower down the level of ROS. Through genetic engineering more tolerant plants are produced which include modification of key genes like transcription factors. In this review article the molecular physiology of plants is discussed where in the factors contributing to stress including biotic and abiotic factors and various mitigation strategies.